2002
DOI: 10.1046/j.1440-1614.2001.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities in mental health, Part 2: an evaluation of the current research effort against stakeholders' priorities

Abstract: It is of concern that committees that evaluate research are guided by different values from consumers and carers in setting priorities. Nevertheless, there is consensus across stakeholder groups that a number of areas should be a high priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 13 publications
3
62
2
Order By: Relevance
“…Loss was not specifically identified in the studies, with the exception of O'Brien who identified 'loss of cultural identity' as a theme [3]. However, evidence of pervasive loss across all areas that surrounded the conceptualization of mental health was consistent across all studies.…”
Section: Lossmentioning
confidence: 85%
“…Loss was not specifically identified in the studies, with the exception of O'Brien who identified 'loss of cultural identity' as a theme [3]. However, evidence of pervasive loss across all areas that surrounded the conceptualization of mental health was consistent across all studies.…”
Section: Lossmentioning
confidence: 85%
“…A theme that came across strongly in this group of people with colitis was that identification of the cause of ulcerative colitis was very important because then the disease could be prevented, cured or treated better. Prevention was also highly rated by consumers of Australian mental health services [10]. A theme that is of direct relevance to clinicians dealing with patients with colitis was the range of symptoms that they attributed to their colitis and which they thought were important research topics.…”
Section: Discussionmentioning
confidence: 99%
“…Literature searches of Medline, CINAHL and PsychInfo and the National Research Register using the keywords 'patients views', 'consumers', 'users priorities', 'users preferences', 'research' and 'involvement' found few primary studies that reported patient views on research topics or their research priorities and none that examined the views of people with inflammatory bowel disease. In the disease areas studied so far, the research priorities of patients have been found to be broad and, where they have been directly compared, they have been found to differ from that of health professionals [7][8][9][10]. For example, in the area of maternity care, the UK National Childbirth Trust initiative [8] showed that consumers prioritized five burning issues including information provision, attitudes and training of midwives, and the withholding of food and drink in labour.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have written persuasively of the importance of gathering and prioritising patients' research questions so that future research assesses the things that matter to patients. 130,131 The James Lind Alliance (JLA) was established in 2004 to encourage patients, carers and clinicians to work together to identify and prioritise shared health-care uncertainties, arguing that medical consensus can be flawed and that research into clinical practice and NHS services should identify and address the uncertainties and investigate the outcomes that are of most practical importance to patients, their carers and clinicians. Research priority themes emerging from the deliberations of JLA partnerships to 2012 (across asthma, incontinence, vitiligo, eczema, stroke, prostate cancer, schizophrenia, aspects of balance and type 1 diabetes) emphasise the assessment of treatments in terms of long-term effects (wanted and unwanted) and safety and adverse effects.…”
Section: Introductionmentioning
confidence: 99%